Effect of water and rice straw management practices on yield and water productivity of irrigated lowland rice in the Central Plain of Thailand - Sumana Maneepitak (2020)
© 2018 Elsevier B.V. Rice cultivation techniques with less irrigation water input are crucial for global food security in the context of changing climate scenarios. Alternate wetting and drying (AWD) is among such water-saving techniques, which could potentially reduce irrigation water input for rice cultivation through alteration of soil submergence period with period of soil non-submergence (unsaturated soil conditions) during the growing season. Rice straw is often scattered in the field after harvest or burned in intensive rice cultivation systems. Response of irrigated lowland rice with respect to grain yield and water use under different water and rice straw management practices largely remains unknown. Field experiments were conducted at the Ayutthaya Rice Research Center, Ayutthaya, Thailand, in two consecutive rice-growing seasons (wet and dry) of 2016–2017 to evaluate the growth, yield and water productivity of irrigated lowland rice under different water and rice straw management practices. The treatments included were two water (continuous flooding [CF] and AWD) and three rice straw management practices (rice straw incorporation [RS-I], rice straw burning [RS-B] and without rice straw incorporation and burning [WRS-I + B]). AWD increased grain yield by 15% in the wet season and by 7% in the dry season compared with CF. Other yield components such as panicle number m–2, spikelet number panicle–1 and 1000-grain weight were also higher under AWD compared with CF depending on the growing season. AWD reduced total water input by 19% in the wet season and by 39% in the dry season resulting in an improvement in total water productivity by 46% in the wet season and by 77% in the dry season relative to CF. Rice straw application either as soil incorporation or open-field burning had no effect on grain yield, water-saving potential and water productivity of the tested variety regardless of the growing season. Although its positive role in supplying plant nutrients and maintaining soil fertility, rice straw incorporation in the field or burning should be discouraged due to negative environmental impacts. AWD (15 cm threshold water level below the soil surface for irrigation or with soil water potential of ≥ −20 kPa [AWD15]) is recommended for irrigated lowland rice cultivation from a point of view of reducing total water input without jeopardizing yield.